2009
DOI: 10.1111/j.1447-0349.2008.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

The feeling of being trapped in and ashamed of one's own body: A qualitative study of women who suffer from eating difficulties

Abstract: The aim of this study was to explore women's bodily experiences of suffering from eating difficulties (ED). The research question was: How do women who suffer from ED experience the bodily aspects related to their condition? Women suffering from ED experience problems in both the physical and emotional areas. Few qualitative studies have specifically addressed sufferers' bodily experiences related to ED. An explorative design was used. The data were collected by means of focus group interviews on the subject o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
(53 reference statements)
4
15
0
3
Order By: Relevance
“…This may be provided in support groups where the participants can interact and reflect on each other's experiences. The latter is in accordance with Rørtveit et al (Rørtveit,Åström, & Severinsson, 2009;Rørtveit, Vevatne, & Severinsson, 2009) who concluded that support groups can be one way to help women with ED, as such groups offer adequate help and make it possible for them to articulate concealed feelings. Barnett et al (2005) argued that group interventions that actively focus on the mother-child relationship may help the mothers to reflect on their difficulties, thus minimising the damage to mother and child.…”
Section: Discussionsupporting
confidence: 85%
“…This may be provided in support groups where the participants can interact and reflect on each other's experiences. The latter is in accordance with Rørtveit et al (Rørtveit,Åström, & Severinsson, 2009;Rørtveit, Vevatne, & Severinsson, 2009) who concluded that support groups can be one way to help women with ED, as such groups offer adequate help and make it possible for them to articulate concealed feelings. Barnett et al (2005) argued that group interventions that actively focus on the mother-child relationship may help the mothers to reflect on their difficulties, thus minimising the damage to mother and child.…”
Section: Discussionsupporting
confidence: 85%
“…Studi ini didasari pada temuan kualitatif pada wanita penderita gangguan makan. Hasil penelitian menemukan bahwa malu yang berfokus pada rasa malu yang berhubungan secara khusus dengan tubuh (malu fisik) lebih berpengaruh daripada rasa malu yang umum (Rørtveit, Åström, & Severinsson, 2009). Satu studi nonklinis lintas-seksional menemukan bahwa malu tubuh adalah prediktor yang lebih kuat dari patologi makan daripada rasa malu umum (Burney & Irwin, 2000).…”
Section: ; Bulimia Nervosa (Bn); Binge Eating Disorder (Bed); Dan Eatunclassified
“…Mengingat banyaknya ragam gangguan makan, maka mengkhususkan pengukuran pada variabel yang menjadi sumber utama munculnya rasa malu dianggap lebih mampu memberikan gambaran penyebab gangguan makan. Malu yang berfokus pada rasa malu yang berhubungan secara khusus dengan tubuh (malu fisik) lebih berpengaruh daripada rasa malu yang umum (Rørtveit, Åström, & Severinsson, 2009). …”
Section: Pembahasanunclassified
“…Women with bulimia nervosa, in contrast, present with several maladaptive thoughts and emotions, low self-esteem, “all or nothing” type of thinking, among others 7,9. Such psychological characteristics imply an inability to develop healthy social networks, since these women have difficulties in interpersonal relationships and are not socially well adjusted 6…”
Section: Introductionmentioning
confidence: 99%